A companion to the historical film - Rosenstone, Robert A.; Parvulescu, Constantin (Malden, MA : Wiley-Blackwell, 2013)
"Broad in scope, this interdisciplinary collection of original scholarship on historical film features essays that explore the many facets of this expanding field and provide a platform for promising avenues of research. Offers a unique collection of cutting edge research that questions the intention behind and influence of historical film. Essays range in scope from inclusive broad-ranging subjects such as political contexts, to focused assessments of individual films and auteurs Prefaced with an introductory survey of the field by its two distinguished editors Features interdisciplinary contributions from scholars in the fields of History, Film Studies, Anthropology, and Cultural and Literary Studies"
Includes bibliographical references and index.
Keywords: Historical films -- History and criticism; Motion pictures and history